Workplace Fear of Missing Out and Telepressure: How Digital Workplace Challenges Contribute to Employee Burnout? - Yücel Efe; İbrahim Yıkılmaz; İlkay Güleryüz (Üniversite Araştırmaları Dergisi)
Information and communication Technologies (ICT) have significantly changed the workplace environment. The rise of remote work and online business processes, especially in the post-pandemic period, has blurred the boundary between work and life balance for many employees, especially academics. The need to respond quickly to messages, e-mails, and work using information and communication technologies has led to an increase in Workplace Telepressure on academics. Increasing demand for information and networks to mitigate the impact of telepressure has led to an increase in workplace FOMO. These two sources of stress have contributed to the burnout experienced by academicians. In this study, the relationship between academicians' WPT, WFOMO, and burnout levels was examined. Data were collected from 286 academicians working in public and private universities using the convenience sampling method. The data were analyzed using SPSS 22 and Smart PLS 4 programs. The study results reveal that the Workplace Telepressure (WPT) levels of academicians have a significant effect on Burnout and Workplace-Fear of Missing Out (WFOMO). Additionally, WFOMO acts as a mediator role in the relationship between WPT and Burnout. These findings expand the existing literature on WPT and WFOMO, two emerging stress factors in the workplace, and provide recommendations for managers and policymakers.